PEDAGOGICAL IDEA OF THEORY BASICS (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article provides information about the word jadid, the theoretical  foundations of jadidism and pedagogical aspects of jadidism, as well as the thoughts m and ideas of our scholars who contributed greatly to the idea of jadidism. Also,  thoughts and comments about how attention is being paid to the idea of Jadidism in  our country today